2009
DOI: 10.1111/j.1552-6569.2009.00365.x
|View full text |Cite
|
Sign up to set email alerts
|

The “Crowned Dens” Revisited: Imaging Findings in Calcium Crystal Deposition Diseases Around the Odontoid

Abstract: The so-called "crowned dens" is a peculiar manifestation of calcium crystal deposition diseases, either caused by calcium pyrophosphate dihydrate or caused by calcium hydroxiapatite crystals, characterized by the presence of calcific deposits around the odontoid, often showing a crown-like configuration on imaging. It has protean clinical and radiological pictures, and care should be taken to avoid misinterpretation and diagnostic errors. Although asymptomatic in many patients, this entity may present as a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Previous reports of CDS have been based on radiographic evidence of calcium deposits around the odontoid process (1), but neck CT is now considered to be the reference standard for making such a diagnosis. The use of radiography this diagnosis is limited due to the superposition of the osseous structure (2). Magnetic resonance imaging is also less useful for the detection of small deposits (2).…”
mentioning
confidence: 99%
“…Previous reports of CDS have been based on radiographic evidence of calcium deposits around the odontoid process (1), but neck CT is now considered to be the reference standard for making such a diagnosis. The use of radiography this diagnosis is limited due to the superposition of the osseous structure (2). Magnetic resonance imaging is also less useful for the detection of small deposits (2).…”
mentioning
confidence: 99%
“…CT is more sensitive and accurate than conventional plain radiography in detecting calcific depositis and bony change. Up to 90% of CT imaging comprises posterior, posterolateral, or circular periodontoid calcification, configuring the "crowned dens" appearance [8]. Plain radiography is often not helpful.…”
Section: Discussionmentioning
confidence: 99%
“…A rare condition, CDS is caused by calcium salt crystal deposition, especially CPPD (1), and a few cases have been reported as having been caused by HA deposition (2). Epidemiology shows that the disease is prevalent in elderly patients, especially in older women (3), and CPPD deposition occurs easily in elderly patients, while HA deposition is more common in younger age groups (40-70 years) (4,5). A review of the published literature revealed that most cases reported are over 60 years old.…”
Section: A1 A2 B Cmentioning
confidence: 99%